2008
DOI: 10.1017/s002531540800009x
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Marphysa (Eunicidae) from the western Cape of South Africa

Abstract: The eunicid polychaete Marphysa sanguinea was until recently believed to be a cosmopolitan species, with a distribution ranging from the south-west coast of England to the Pacific coast of America, and New Zealand and Australia in the western Pacific. However, there are many morphological and ecological inter-population differences that render the definitive identification of these numerous populations difficult. The recent designation of a neotype, together with a more detailed morphological description of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 34 publications
7
54
0
2
Order By: Relevance
“…Recently, Hutchings and Karageorgopoulos (2003) redescribed Marphysa sanguinea using a specimen collected in England as the type locality. Subsequent taxonomic revisions of the Marphysa sanguinea group have been done from different parts of the world (Lewis and Karageorgopoulos, 2008;Glasby and Hutchings, 2010). Lewis and Karageorgopoulos (2008) reported that there is sufficient genetic differentiation between the geographically separated populations of Australia, England, Japan, Portugal, and South Africa, suggesting that Marphysa sanguinea does not occur in Japan.…”
Section: Pseudopotamilla Occelata Moore 1905mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hutchings and Karageorgopoulos (2003) redescribed Marphysa sanguinea using a specimen collected in England as the type locality. Subsequent taxonomic revisions of the Marphysa sanguinea group have been done from different parts of the world (Lewis and Karageorgopoulos, 2008;Glasby and Hutchings, 2010). Lewis and Karageorgopoulos (2008) reported that there is sufficient genetic differentiation between the geographically separated populations of Australia, England, Japan, Portugal, and South Africa, suggesting that Marphysa sanguinea does not occur in Japan.…”
Section: Pseudopotamilla Occelata Moore 1905mentioning
confidence: 99%
“…Subsequent taxonomic revisions of the Marphysa sanguinea group have been done from different parts of the world (Lewis and Karageorgopoulos, 2008;Glasby and Hutchings, 2010). Lewis and Karageorgopoulos (2008) reported that there is sufficient genetic differentiation between the geographically separated populations of Australia, England, Japan, Portugal, and South Africa, suggesting that Marphysa sanguinea does not occur in Japan. More recently, Taru (2013) recognized Marphysa iwamushi as a valid species.…”
Section: Pseudopotamilla Occelata Moore 1905mentioning
confidence: 99%
“…Hutchings and Karageorgopoulos (2003) suggest that the distribution of M. sanguinea is restricted to northern Europe, and that records from other parts of the world should be checked. Certainly, the records of M. sanguinea from South Africa have been found to represent another species (Lewis and Karageorgopoulos, 2008), and this has been confirmed both morphologically and molecularly. …”
Section: Discussionmentioning
confidence: 75%
“…One is M. sanguinea Montagu, 1813, which has been reported from all oceans of both northern and southern hemispheres, except for the polar regions (see Day, 1967;Miura, 1977;Gathof, 1984;Paxton and Chou, 2000;Prevedelli et al, 2007). However, Hutchings and Karageorgopoulos (2003), as well as Lewis and Karageorgopoulos (2008), have challenged the cosmopolitan status of M. sanguinea. Hutchings and Karageorgopoulos (2003) suggest that the distribution of M. sanguinea is restricted to northern Europe, and that records from other parts of the world should be checked.…”
Section: Discussionmentioning
confidence: 99%
“…However, voucher specimens for many populations do not exist or were poorly identified. Taxonomists have recently reexamined many of these specimens, concluding that they may be a few to several different sibling species (Hutchings and Karageorgopoulos 2003, Prevedelli et al 2007, Lewis and Karageorgopoulos 2008. All literature referring to M. sanguinea and its biology should therefore be referred to with caution.…”
Section: Introductionmentioning
confidence: 99%